The extent of the neurocognitive impairment in elderly survivors of war suffering from PTSD: meta-analysis and literature review - Yasir Rehman (AIMS Neuroscience, 2021)
Objectives: We performed a meta-analysis and systematic review on elderly survivors of war suffering from PTSD to estimate the variability in their cognitive impairment based on individual neuropsychological tests. Methods: We included case control studies that explored the association of cognitive deficits in elderly PTSD civilian survivor of wars (age >60 years), using MEDLINE, Embase and PsycINFO from the inception to January 2018. We compared the cognitive performances in three comparisons i) PTSD+ vs. PTSD− civilian survivors of war; ii) PTSD+ vs. Control and iii) PTSD− vs. Control. The risk of bias was assessed using the Newcastle-Ottawa Scale for case-control studies. Results: Out of 2939 bs and abstracts, 13 studies were eligible for data extraction. As compared to PTSD− civilian survivors of war, PTSD+ civilian survivors of war demonstrated significant deficits on TMT-A, TMT-B, Digit span backward, explicit memory low pair associate, CVLT recognition, WAIS-verbal and non-verbal tests. As compared to health controls, PTSD+ survivors demonstrated significantly lower performance on explicit memory low pair and high associate, RAVLT immediate and delayed recall, CVLT delayed and short cued recall. Performance on the neuropsychological test between PTSD− survivors of war and controls was not significant for all tests. Conclusion: The pattern suggests that PTSD+ survivors of war had poorer performance in tasks requiring processing speed, executive function, attention, working memory and learning. The magnitude of the cognitive deficits in our pooled analysis was small to moderate depending on the neuropsychological test. Most of our pooled analysis suffered from a high risk of bias, which lowered the confidence in our results.